The Change Project Approach: A response for reorienting teacher education to address Education 2030 in southern Africa – The case of Midlands State University, Zimbabwe - Urenje, Shepherd; Chauraya, Million; Chikunda, Charles (The EEASA President, 2022)
The change project approach could be applied to enhance teacher education for the purpose of confronting 21st Century challenges through education (Education 2030). The challenge for teacher education institutions is to prepare future teachers with the socio-ecological knowledge, skills, attitudes and values essential for sustainable living, by reorienting current unsustainable ways of thinking and doing. This can be achieved by integrating Education for Sustainable Development (ESD) and in a number of teacher education programmes in southern Africa, teacher educators have begun to do this. This paper discusses the critical role of a change project approach in creating the social transformation processes and actions required to achieve the ambitions of Education 2030. Cases from the Midlands State University in Zimbabwe have demonstrated important efforts to reorient university curricula. The paper investigates and discusses the challenges associated with reimagining teacher education and key considerations that need to be addressed to achieve the goal of Agenda 2030.